Frequency and Time Domain Analysis of Planar UWB Antenna Controllable WIMAX/WLAN Band-Notched Characteristics - Rajarshi Sanyal; Debashree Bhowmik; Partha P. Sarkar; Santosh K. Chowdhury, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An ultra wideband (UWB) printed monopole antenna with dual band stop characteristics is proposed in this article. Distinctive feature of this antenna is the notched band control ability with improved operating bandwidth. By employing modified lambda/2 vertically combined T and U-shaped conductor backed plane, a sharp band notch is achieved with notched band of 3.3– 3.7 GHz. In order to obtain another notched frequency band of 5.1-6 GHz, a rectangular spiral shaped lambda/4 open stub has been incorporated to the microstrip feed line. Frequency rejection performance can be controlled flexibly by varying various parameters and positions of the corresponding band notched elements. Furthermore, additional resonance at higher frequencies has been generated by introducing a metal loaded complimentary split ring resonator (MLCSRR) to the ground plane, so that it provides enhanced usable fractional bandwidth (2.6-13.9 GHz) more than 136%. The performance of the proposed antenna is analyzed both in frequency and time domain to assess its suitability in UWB communication.